Assessment of the mechanism of excessive deformations encountered in a large-span tunnel excavation using analytical and 3D numerical analyses - Aygar, Ebu Bekir; Gokceoglu, Candan (Italian journal of engineering geology and environment, 2024)
T8 tunnel (L=3826 m) is located in Dogancay Section in Ankara-İstanbul High Speed Railway Project. The tunnel was designed and excavated with New Austrian Tunnelling Method (NATM). The tunnel route was composed of granite, mudstone, and shale units. A part of the tunnel route between km:142+280 - 142+360 contains landslides. While determining the tunnel route, it is desirable to avoid landslides as much as possible. However, due to the geometrical restrictions of a high-speed railway, it is necessary to pass through the landslide or parts close to the landslide. As part of the Ankara-Istanbul High-Speed Railway Project, the T8 tunnel, the construction of which was completed in Adapazarı, Doğançay section, was excavated under landslides. As a result of the geotechnical investigations including borehole and in-situ tests, the tunnel roof altitude was designed to be 10 m below the failure surface of the landslide. During the excavation in this region in the tunnel, excessive deformations occurred in places that exceeded the maximum deformation tolerance of 15 cm. However, tunnel stability was achieved with improvements and additional support. The purposes of the study are to explain the excessive deformations that occurred during the excavation stage and to understand the effect of the landslide on these deformations using analytical and 3D numerical analyses. Within the purpose of the study, the relationship between a tunnel and a landslide is investigated, and support systems for these types of problems are described. The results showed that the main source of the excessive deformations and failures in the tunnel is due to the high horizontal pressures caused by the landslide material on the surface. Consequently, the results of the study may provide a scientific basis for the optimum support design of tunnel construction under landslides.